Colloidal polypyrrole as binder for silicon anode in lithium ion batteries. Issue 4 (5th April 2022) - Avcı Yayla, Işık İpek; Yuca, Neslihan; Sezer, Esma; Ustamehmetoğlu, Belkıs
Abstract: Silicon (Si)‐based anodes have limited application in lithium ion batteries (LIBs) due to the loss of contact with current collector because of large volume change during lithiation and delithiation processes. In this study, pyrrole (Py) was polymerized chemically by cerium ammonium nitrate (CAN) and conductive colloidal polypyrrole (Col‐PPy) was obtained in one step in N, N′‐dimethylformamide (DMF). To overcome problems during the volume change, Col‐PPy was then used as polymeric binder with Si nanoparticle (SiNP) in Si‐anode and it called as "Col‐PPy/SiNP." In order to improve the cyclability and capacity of Si‐anodes, Col‐PPy solution was used also together with polyvinylidenefluoride (PVDF) and polyvinylpyrrolidone (PVP). These Si‐anodes were further analyzed with cycle tests and combined cycle tests at different rates (C‐rate) in half cells and scanning electron microscopy images of electrodes were taken before and after cycling. All results suggested that as an anode for LIB, Col‐PPy/SiNP exhibited high reversible capacity (2617 mAh/g at C/10 [0.42 A/g]) and good cycling performance (reversible capacity of 1400 mAh/g after 189 cycles at C/3 [1.4 A/g]).